Effect of β-Blocker Cessation on Chronotropic Incompetence and Exercise Tolerance in Patients With Advanced Heart Failure - Hirsh, Benjamin J.; Mignatti, Andrea; Garan, A. Reshad; Uriel, Nir; Colombo, Paolo; Sims, Daniel B.; Jorde, Ulrich P. (Circulation. Heart failure, 2012)
Chronotropic incompetence is defined as the inability to reach 80% of heart rate (HR) reserve or 80% of the maximally predicted HR during exercise. The presence of chronotropic incompetence is associated with reduced peak oxygen consumption, and rate-responsive pacing therapy is under investigation to improve exercise capacity in heart failure (HF). However, uncertainty exists about whether chronotropic incompetence and reduced exercise tolerance in HF are attributable to β-blockade. Subjects with HF and receiving long-term β-blocker therapy underwent cardiopulmonary exercise tolerance testing under 2 conditions in random sequence: (1) after a 27-hour washout period (Off-BB) and (2) 3 hours after β-blocker ingestion (On-BB). Norepinephrine levels were drawn at rest and at peak exercise. β1-response to norepinephrine was assessed using the chronotropic responsiveness index: ΔHR/Δlog norepinephrine. Nineteen patients with systolic HF (left ventricular ejection fraction, 22.8±7.7%) were enrolled. Mean age was 49.4±12.3 years. Average carvedilol equivalent dose was 29.1±17.0 mg daily. Peak HR off/on β-blockers was 62.7±18.7% and 51.4±18.2% HR reserve (P<0.01) and 79.1±11.0% and 70.3±12.3% maximally predicted HR (P<0.01). For the Off-BB and On-BB conditions, the respiratory exchange ratios were 1.05±0.06 and 1.05±0.10 (P=0.77), respectively, confirming maximal and near identical effort in both conditions. The peak oxygen consumption was 16.6±3.34 and 15.9±3.31 mL/kg/min (P=0.03), and the chronotropic responsiveness index was 19.3±7.2 and 16.2±7.1 (P=0.18). Acute β-blocker cessation does not normalize the chronotropic response to exercise in patients with advanced HF and chronotropic incompetence.